Review on Plasma-Assisted Ignition Systems for Internal Combustion Engine Application - Yong Hyun Choi; Joonsik Hwang (Energies, 2023)
Due to the depletion of conventional petroleum-based fuels and increasing environmental concerns, industries have been developing new combustion technologies with acceptable cost ranges and minimum system modifications for consumers. Among many approaches, the utilization of plasma ignition systems is considered as a promising pathway to achieve greener transportation while maintaining conventional internal combustion engine systems. Plasma contains highly reactive radicals, and those have a great potential of enhancing chemical reactions that are beneficial for reducing carbon emissions. The primary objective of this paper is to provide an overview of currently available plasma-assisted combustion systems including recent achievements in research and development, and technical challenges for successfully implementing a new ignition system. This review will introduce various plasma-assisted combustion approaches from worldwide projects, covering non-thermal and thermal plasma systems in internal combustion engines.